Design and Development of a Complaint Information System at Mts Nahdlatul Ulama Adabul Hafazhah Based on Laravel - Nina Felisa (CV. Edutechnium Indonesia, 2025)
The student complaint system at MTs Nahdlatul Ulama Adabul Hafazhah serves as an important medium for reporting grievances and issues during school activities. The existing manual system, which relies on direct or verbal submissions, often leads to slow responses, lack of documentation, and reluctance to report. This study develops a web-based complaint information system using the Laravel framework and the Waterfall method, covering the stages of analysis, design, implementation, and testing. The system is designed with MVC architecture, UML modeling, and a user interface created in Figma. Key features include complaint submission, management, follow-up, tracking, feedback, and statistical reporting. Blackbox Testing results show all functions operate effectively. The system is expected to enhance transparency, speed up handling, and foster a safer, more conducive learning environment.